THE INFLUENCE OF GREEN OPEN SPACES ON USER HAPPINESS IN APSARI PARK SURABAYA - Irdiansyah, Achmad Najma; Artanti, Daffa Maulidia; Sulaiman, Shania Zahra Rizqitta; Wijaya, Ravinda Arga; Syawalita, Tsanya Kamila; Harmunisa, Yusvika Ratri (ADBE, 2025)
The COVID-19 pandemic has changed perspectives in public space design, creating new challenges that require innovation to adapt post-pandemic. In Indonesia, adjusting to this situation calls for creative thinking in designing open-space architecture, especially urban parks crucial for community well-being. This research aims to understand the influence of green open-space design on user comfort and happiness at Apsari Park, Surabaya, as a response to the post-pandemic impact on social interaction and community welfare. Through comprehensive research methods including field observations, interviews, and document analysis, data were collected to grasp user perceptions and experiences. The research findings emphasize the importance of factors such as diverse vegetation composition, ergonomic spatial arrangements, easy accessibility, and varied recreational facilities in enhancing user comfort and happiness. In-depth analysis shows that effective integration of green open-space design not only creates a physically comfortable environment but also affects visitors' psychological well-being, increasing feelings of happiness, relaxation, and connection with nature. Hopefully, this study's results can guide future health architecture designs effectively.